Satellite derived bathymetry (sbd) of inaccessible water: an application of log-transformed band ratio model - Nag, Kamal (Acta Geographica Debrecina Landscape & Environment series, 2025)
The present study applied log transformed Band Ratio Model (BRM) on Sentinel-2A image of Copernicus programme of European Space Agency (ESA) to derive shallow water bathymetric map in a part of Indian eastern coast. The “empirical bathymetry processor” in SNAP software of ESA has been used for this purpose. General Bathymetric Chart of the Ocean (GEBCO)_2020 of Nippon Foundation has been taken as a reference image for point data input. Log transformed ratio of band-2 and ban-3 of Sentinel-2A at 10 m spatial resolution enables bathymetric mapping of nearshore water. Before applying BRM, image processing involves land mask, sun glint correction and dark object subtraction (DOS). This approach can be used as an alternative to conventional hydrographic survey for bathymetric mapping in inaccessible water with great savings of cost and time.